2019
DOI: 10.11565/arsmed.v44i1.1479
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización clínico-epidemiológica de mordeduras en personas mayores en la provincia de los Andes, región de Valparaíso, Chile

Abstract: Introducción: las mordeduras constituyen un relevante problema de salud, con amplio espectro clínico, pudiendo causar la muerte. Existe escasa información del tema en personas mayores (PM). Método: análisis de base de datos realizada a partir de formularios de notificación de mordeduras de centros de salud y de Protocolos de Denuncia de Animal Mordedor en la provincia de Los Andes, Chile.Objetivo: caracterizar epidemiológicamente las mordeduras en personas mayores ocurridas en la provincia de Los Andes, V regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(6 reference statements)
3
1
1
Order By: Relevance
“…In relation to the victim’s gender, men were bitten more than women, which is consistent with previous studies in other countries, such as the United States [ 68 , 69 ], Korea [ 37 ], Bosnia and Herzegovina [ 38 ], Iran [ 69 ] and Ireland [ 70 ]; as well as with previous Chilean publications [ 23 , 34 , 44 , 71 ]. These results can be explained because men can have a more invasive type of approach with the animal, they can also be less cautious or have less perception of an eventual threat.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In relation to the victim’s gender, men were bitten more than women, which is consistent with previous studies in other countries, such as the United States [ 68 , 69 ], Korea [ 37 ], Bosnia and Herzegovina [ 38 ], Iran [ 69 ] and Ireland [ 70 ]; as well as with previous Chilean publications [ 23 , 34 , 44 , 71 ]. These results can be explained because men can have a more invasive type of approach with the animal, they can also be less cautious or have less perception of an eventual threat.…”
Section: Discussionsupporting
confidence: 91%
“…The highest number of canine attacks was registered in winter and autumn, which differs from most of the previous studies in the country, where a higher frequency of incidents was reported in summer [ 34 , 44 , 71 ]. It also differs from international publications, where a higher concentration of bites is reported in spring [ 38 ] or summer [ 52 ].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Accidents due to animal bites are an important national and international public health problem, both due to their frequency and their health care requirements, affecting children and adults regardless of socioeconomic status [ 1 ]. The dog is the animal most frequently involved in this type of incident [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%